KARAKTERISTIK PENDERITA HIPERTENSI YANG DIRAWAT INAP DI RUMAH SAKIT UMUM DAERAH SIDIKALANG TAHUN 2010-2012 - Ria Arihta Ujung; drh. Rasmaliah, M.Kes; Drs. Jemadi, M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Hypertyension is one of the degenerative disease a public health problem and important risk factor to arise many ailment of vital organ and bring a weakness of physical, blemish and mortality. Hypertension often called as silent killer because often appears without symptoms, while the blood pressure out of normal. Health Research Association (Riskesdas) Balitbangkes in 2007 showed the prevalence of hypertension nationally reached 31,7%. According to Rasmaliah and friends research in 2004 in work area of Puskesmas Pekan Labuhan, Medan Labuhan, incidens rate of hypertension for people who above 26 years old is 26,4% and patiens of yipertension more in 45-60 years old reached 30,8%. To know the charecteristics of patiens who are hospitalized at General Hospital of  Sidikalang, descriptive study has been done by using case series design and continued with the statistical analysis. The samples were 213 data of patients. From the record data, the result obtained by the higest proportion of female patiens in the age group >60 years (30,0%), Protestant (72,8%), house wives (30,8%), in Dairi (85,9%), second degree of hypertension (79,3%), without comorbidity (56,8%), dyspepsia (54,3%), stroke (53,8), average length of stay 3,45 days, askes (48,4), medically discharged and becoming out patients (81,7). There is no significant  difference between ages with the degree of hypertension (p=0,600). There is no significant  difference between sexes with the degree of hypertension (p=0,087). There is no significant difference between jobs with the degree of hypertension (p=0,716). There is  a difference significant between  average length of stay with the degree of hypertension (p=0,000). To General Hospital of Sidikalang that complement education data recording hospitalized patiens. Give a health promotion to communities to should be empowered, through education in order to contribute active to the prevention and contol of hypertension. To hipertensive patients for his blood pressure checked regurally and maintain a diet and a healthy life style. Keywords : hypertension, patient characteristics, General Hospital of Sidikalang